Alternative Measures of Political Efficacy: The Quest for Cross-Cultural Invariance With Ordinally Scaled Survey Items - Scotto, Thomas J.; Xena, Carla; Reifler, Jason (Frontiers in Political Science, 2021)
In this paper, we examine the measurement of citizens’ beliefs that politicians and political systems are responsive (external efficacy) and that citizens see themselves sufficiently skilled to participate in politics (internal efficacy). This paper demonstrates techniques that allow researchers to establish the cross-context validity of conceptually important ordinal scales. In so doing, we show an alternative set of efficacy indicators to those commonly appearing on cross-national surveys to be more promising from a validity standpoint. Through detailed discussion and application of multi-group analysis for ordinal measures, we demonstrate that a measurement model linking latent internal and external efficacy factors performs well in configural and parameter invariance testing when applied to representative samples of respondents in the United States and Great Britain. With near full invariance achieved, differences in latent variable means are meaningful and British respondents are shown to have lower levels of both forms of efficacy than their American counterparts. We argue that this technique may be particularly valuable for scholars who wish to establish the suitability of ordinal scales for direct comparison across nations or cultures.